Crystallographic features of orbital ordering related to the C-type antiferromagnetic state in the simple perovskite manganite Ca1-xPrxMnO3. Issue 9 (2016) - Kojima, Kentaro; Inoue, Yasuhide; Koyama, Yasumasa
ABSTRACT: In the highly-correlated electronic system Ca1- x Pr x MnO3 having the simple perovskite structure, it has been reported that there exists the C-type orbital-ordered (COO) state accompanying an antiferromagnetic ordering for 0.10 ≤ x ≤ 0.25. According to the previous studies concerning orbital-ordered states in simple perovskite manganites, the COO state was understood to be characterized by a spatial array of (3z 2 -r 2 )-type orbitals for 3d electrons in Mn ions. The notable feature of the COO state in Ca1- x Pr x MnO3 is that the state with the monoclinic-P21 /m symmetry appears as a result of the structural transition from the disordered state with the orthorhombic-Pnma symmetry. Compared with the COO-state formation from the cubic-Pm $\overline 3$ m state, however, the formation from the disordered-Pnma state has not been understood yet. We have thus examined the crystallographic features of the formation of the COO state in Ca1- x Pr x MnO3, mainly by x-ray powder diffraction and transmission electron microscopy. In the case of x = 0.16, for instance, the COO state was found to appear from the disordered-Pnma state around 90 K on cooling. The notable feature of the formation is that, in the Pnma state just before the COO-state formation, characteristic diffuse scattering appeared around each reflection in electron diffraction patterns, together with the splitting of the 200c reflection in x-ray powder diffraction profiles in the pseudo-cubic notation. Based on these experimental data, it is understood that the formation of the COO state in Ca1- x Pr x MnO3 accompanies remarkable fluctuations of the C-type orbital ordering in the disordered-Pnma state.